The Effect of an 8-Week Yoga Training Program on Balance and Knee Proprioception After Mental Fatigue in Amateur Male Athletes - Mohammad Sarhad Hasan; Manochehr Haydary; Farzaneh Gandomi (Biyumikānīk-i varzishī, 2020)
Objective: Mental fatigue is caused by long-term cognitive activities and lead to changes in motor coordination. The purpose of this study was to investigate the effect of yoga training on balance and knee proprioception after mental fatigue in amateur male athletes. Methods: In this quasi-experimental study, 36 amateur male students were voluntarily selected as study samples and randomly divided into training (n=18) and control (n=18) groups. The training group received yoga exercises for eight weeks, three sessions per week, each for one hour. Mental fatigue was induced by 45 minutes of cognitive activity (Stroop test). Before and after mental fatigue and intervention, their dynamic balance was measured by Y-balance test and the semi-dynamic balance by Lafayette stability platform. Data were analyzed in SPSS v.22 software using paired sample t-test at the significant level of 0.05. Results: The effects of time and group×time interaction on dynamic and semi-dynamic balances (P=0.0001), and on active and passive knee proprioception (P=0.0001) were significant after yoga training. Conclusion: There were significant improvements in balance and knee proprioception of amateur athletes after yoga training. Further studies should be conducted to introduce solutions to the occurrence of mental fatigue in these athletes.